Ferulic acid exerts neuroprotective effects against cerebral ischemia/reperfusion-induced injury via antioxidant and anti-apoptotic mechanisms in vitro and in vivo - Ren, Zhongkun; Zhang, Rongping; Li, Yuanyuan; Li, Yu; Yang, Zhiyong; Yang, Hui (International journal of molecular medicine, 2017)
Ferulic acid (FA) is a derivative of cinnamic acid. It is used in the treatment of heart head blood-vessel disease and exerts protective effects against hypoxia/ischemia-induced cell injury in the brain. This study investigated the potential neuroprotective effects of FA against ischemia/reperfusion (I/R)-induced brain injury in vivo and in vitro through hematoxylin and eosin (H&E) and Nissl staining assays, flow cytometry, Hoechst 33258 staining, quantitative PCR, western blot analysis and fluorescence microscopic analysis. In this study, models of cerebral I/R injury were established using rats and pheochromocytoma (PC-12) cells. The results revealed that treatment with FA significantly attenuated memory impairment, and reduced hippocampal neuronal apoptosis and oxidative stress in a dose-dependent manner. The results from in vitro experiments also indicated that FA protected the PC-12 cells against I/R-induced reactive oxygen species (ROS) generation and apoptosis by inhibiting apoptosis, Ca2+ influx, superoxide anion (O2−), malondialdehyde (MDA) and glutathione peroxidase (GSH-Px) production in a concentration-dependent manner. Moreover, FA inactivated the Toll-like receptor (TLR)/myeloid differentiation factor 88 (MyD88) pathway. MyD88 overexpression abolished the neuroprotective effects of FA. On the whole, we found that FA attenuated memory dysfunction and exerted protective effects against oxidative stress and apoptosis induced by I/R injury by inhibiting the TLR4/MyD88 signaling pathway. This study supports the view that FA may be a promising neuroprotective agent for use in the treatment of cerebral ischemia.